2012
DOI: 10.1097/gme.0b013e318258aad7
|View full text |Cite
|
Sign up to set email alerts
|

Association of 11β-hydroxysteroid dehydrogenase type I expression and activity with estrogen receptor β in adipose tissue from postmenopausal women

Abstract: We conclude that, in adipose tissue, ER-β-mediated estrogen signaling can up-regulate 11βHSD1 and that this may be of particular importance in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 22 publications
2
18
4
Order By: Relevance
“…One cross-sectional study reported that ERβ, but not ERα, was higher in postmenopausal compared to premenopausal women [19]. In the present study we found no differences in adipose tissue ERα and ERβ in late compared to early postmenopausal women.…”
Section: Discussioncontrasting
confidence: 63%
“…One cross-sectional study reported that ERβ, but not ERα, was higher in postmenopausal compared to premenopausal women [19]. In the present study we found no differences in adipose tissue ERα and ERβ in late compared to early postmenopausal women.…”
Section: Discussioncontrasting
confidence: 63%
“…The mechanisms remain unknown in humans. However, E 2 may increase 11-␤-hydroxysteroid dehydrogenase type 1, leading to conversion of cortisone to cortisol, which in turn inhibits ACTH through negative feedback (20). Estrogen administration in ovariectomized rats mutes glucocorticoid negative feedback, resulting in higher ACTH levels, whether corticosterone or a synthetic glucocorticoid is administered by single bolus injection to test fast feedback via nongenomic mechanisms (25) or infused continuously to test slow feedback via nuclear glucocorticoid receptors (4).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of ER receptors in tissues other than SAT suggest there may be declines in ER expression with increasing age [4], but age-related reductions in ER have not yet been reported in human SAT. In fact, one study reported higher, not lower, abdominal SAT ERβ expression in postmenopausal compared to premenopausal women [6]. Such menopause-related differences in ER expression could be the result of aging, estrogen deficiency, or changes in body fat distribution, but to our knowledge this has not yet been studied.…”
Section: Introductionmentioning
confidence: 88%